Accurate diagnosis of multicomponent Babuviruses infecting abaca by simultaneous amplification of their genome segments - Barbosa, Cris Francis C.; Aquino, Vermando M.; Koh, Rhosener Bhea L.; Galvez, Leny C. (2020)
Abaca bunchy top virus and banana bunchy top virus (ABTV and BBTV; genus Babuvirus; Family: Nanoviridae) are two of the most destructive abaca viruses. Uniplex polymerase chain reaction (PCR) and loop-mediated isothermal amplification (LAMP) are nucleic acid amplification techniques (NAATs) currently being used for their detection and diagnosis. However, the multicomponent nature of these bunchy top viruses has been documented to affect the diagnostic sensitivity of the aforementioned techniques, resulting in false-negative detection. This study, therefore, aimed to develop an assay that is strategic for accurate diagnosis of these multicomponent viruses. The multiplex PCR method was optimized at 56.5 °C annealing temperature (TA), and was evaluated to have 91?100% diagnostic sensitivity and diagnostic specificity (CI = 95%, n = 60) against ABTV and BBTV ? more accurate than LAMP and uniplex PCR. This paper provides evidence on the effect of the multicomponent nature of ABTV and BBTV in their detection even on techniques with superior analytical sensitivity such as LAMP. Moreover, it provides a strategic diagnostic tool to circumvent difficulties in the diagnosis of multicomponent abaca viruses. (Author's abstract)